The role of zakat in the provision of social protection: A comparison between Jordan, Palestine and Sudan - Anna Carolina Machado; Charlotte Bilo; Imane Helmy (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
Zakat is one of the five pillars of Islam and can be understood as a form of religious duty, purifying one's wealth and at the same time functioning as a means to redistribute wealth to those in need. In Arabic, zakat means, among others, growth and purity (Dean and Khan 1997). In Muslim-majority countries, it has a long tradition of providing income, goods for consumption and other basic services such as health care and education to poor and marginalised populations. A growing body of research has investigated the role of zakat in the provision of social protection - understood here as income and in-kind transfers with the aim of protecting vulnerable people against risks - and its importance as a poverty reduction mechanism (see Ali 2014; Hassan 2010; Hassanain and Saaid 2016; Ibrahim and Ghazali 2014). Although much of the criticism of zakat institutions evolves around their lack of coordination, efficiency and transparency (Johari, Ali, and Aziz 2015), zakat has several advantages when it comes to assisting poor people. In countries where the State provides limited social protection - due to ongoing conflicts, for example - zakat can play a crucial role in providing support to those in need. [...]
Keywords: 330; Role; zakat; provision; social protection; comparison; Jordan; Palestine; Sudan